Propensity for Risk Taking Across the Life Span and Around the Globe. (February 2016) - Mata, Rui; Josef, Anika K.; Hertwig, Ralph
Past empirical work suggests that aging is associated with decreases in risk taking. But are such effects universal? Life-history theory suggests that the link between age and risk taking is a function of specific reproductive strategies that can be more or less risky depending on the ecology. We assessed variation in the age-risk curve using World Values Survey data from 77 countries ( N = 147, 118). The results suggest that propensity for risk taking tends to decline across the life span in the vast majority of countries. In addition, there is systematic variation among countries: Countries in which hardship (e.g., high infant mortality) is higher are characterized by higher levels of risk taking and flatter age-risk curves. These findings suggest that hardship may function as a cue to guide life-history strategies. Age-risk relations thus cannot be understood without reference to the demands and affordances of the environment.